Impact of electronic imaging on clinician behavior in the urgent care setting...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Mattern CWT; Erickson BJ; King BF Jr.; Okryznski TW (Journal of Digital Imaging)
Although it is intuitively valuable that more expedient delivery of radiographic images and reports to clinicians would improve patient care, it is important to document these outcomes to validate further advances in these areas. We evaluated the care of 215 patients seen at a walk-in clinic to determine what benefit digital imaging is to the patient. Cohorts consisted of all patients for whom specified radiology examinations were ordered during a 7-day period. The first cohort was recruited when analog films were used. The second cohort received examinations performed with computed radiography (CR) acquisition and computer display, which had been in use for 2 years. Patients were categorized as to the type of study they received, as well as whether a staff radiologist was immediately available to read the study. Clinical behavior was characterized by outcome measures of time to final diagnosis, time to final treatment, and need for follow-up. Our analysis demonstrated a reduction in time to final diagnosis that was better appreciated during the times when a staff radiologist was not immediately available. It also suggested that greater time reductions were seen for patients who received extremity examinations than those who received chest, sinus, or rib films. These data suggest that digital imaging is a useful tool to improve clinical outcome of patients seen in the acute care setting. Copyright (c) 1999 by W.B. Saunders Company